International networking capability on international marketing performance of Thai garment entrepreneur in CLMV market - Kasornbua, Thichakorn; Phimolsathien, Thepparat (My University, 2017)
This research had an objective to study an influence of the international networking capability on the international marketing performance of Thai garment industry in CLMV markets. Data were collected from the entrepreneurs, company owner and international affairs manager of garment industry 204 cases using multiple regression analysis. The research’s result showed the factors in the international networking capability that had the influence on the international marketing performance comprising 3 factors as partner knowledge, relation skills, and coordination respectively. These 3 factors had the positive influence on the international marketing performance. Referring to the research findings, we recommended that in case the entrepreneurs required being in CLMV markets, they should emphasize the importance of partner knowledge mostly. Reasoning, the rules, and regulations relating to the foreign entrepreneurs in CLMV markets were inadequately encouraged.
Keywords: Garment; International marketing performance; International networking capability